Aristotle as an ichthyologist: Exploring Aegean fish diversity 2, 400 years ago. Issue 6 (14th May 2017) - Ganias, Kostas; Mezarli, Charikleia; Voultsiadou, Eleni
Abstract: In an attempt to trace the origins of the science of ichthyology, we studied Aristotle's zoological works (21 books in total), aiming to give an exhaustive catalogue of his fishes, suitable for use by modern marine biologists, and to evaluate the great philosopher's knowledge of fish biology. Our investigation yielded 135 ichthyonyms used to describe 109 individual fish taxa (13 fishes had multiple names) and 12 terms that corresponded either to fish developmental stages or behavioural patterns. Because of the variable amount of information given in the texts, 54 fishes were identified to species or genus level, 24 fishes to higher categories (family, order), 27 fishes could only be classified as Actinopterygii or Elasmobranchii, while four could not be classified at all. Among the most easily recognizable fishes were Lophius spp., Conger conger, Muraena helena, Anguilla anguilla and Mugil cephalus . The latter two and the tunas ( Τhunnus spp.) were the most frequently recorded fishes. Aristotle's inquiry was not limited or focused on fish that were of human interest, but he also reported or described species that fascinated him by their peculiar life history. He was interested in a wide array of aspects of fish biology ranging from body structure and function, reproduction and development to fish feeding habits, migrations and diseases. As evidenced by his work, Aristotle should be considered the first ichthyologist, preoccupied with the zoological, scientific study of fish, and a review of his writings can prove useful for current ichthyological research.